Targeted protein degradation through site-specific antibody conjugation with mannose 6-phosphate glycan - Kaori Mukai; Robert Cost; Xin Sheen Zhang; Emily Condiff; Joanne Cotton; Xiaohua Liu; Ekaterina Boudanova; Björn Niebel; Peter Piepenhagen; Xinming Cai; Anna Park; Qun Zhou (mAbs)
Recent developments in targeted protein degradation have provided great opportunities to eliminating extracellular protein targets using potential therapies with unique mechanisms of action and pharmacology. Among them, Lysosome-Targeting Chimeras (LYTACs) acting through mannose 6-phosphate receptor (M6PR) have been shown to facilitate degradation of several soluble and membrane-associated proteins in lysosomes with high efficiency. Herein we have developed a novel site-specific antibody conjugation approach to generate antibody mannose 6-phosphate (M6P) conjugates. The method uses a high affinity synthetic M6P glycan, bisM6P, that is coupled to an Fc-engineered antibody NNAS. This mutant without any effector function was generated by switching the native glycosylation site from position 297 to 298 converting non-sialylated structures to highly sialylated N-glycans. The sialic acid of the glycans attached to Asn298 in the engineered antibody was selectively conjugated to bisM6P without chemoenzymatic modification, which is often used for site-specific antibody conjugation through glycans. The conjugate is mainly homogeneous by analysis using mass spectrometry, typically with one or two glycans coupled. The M6P-conjugated antibody against a protein of interest (POI) efficiently internalized targeted soluble proteins, such as human tumor necrosis factor (TNF), in both cancer cell lines and human immune cells, through the endo-lysosomal pathway as demonstrated by confocal microscopy and flow cytometry. TNF in cell culture media was significantly depleted after the cells were incubated with the M6P-conjugated antibody. TNF internalization is mediated through M6PR, and it is correlated well with cell surface expression of cation-independent M6PR (CI-MPR) in immune cells. A significant amount of CI-MPR remains on the cell surface, while internalized TNF is degraded in lysosomes. Thus, the antibody-M6P conjugate is highly efficient in inducing internalization and subsequent lysosome-mediated protein degradation. Our platform provides a unique method for producing biologics-based degraders that may be used to treat diseases through event-driven pharmacology, thereby addressing unmet medical needs.